The concentration of trace and toxic elements in the hair and in plasma of children with the autism spectrum disorder - Szabat, Przemysław; Poleszak, Julita; Szabat, Marta; Boreński, Grzegorz; Wójcik, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2019)
Introduction: Explanation of pathogenesis and selection of an effective therapeutic form to treat children with autism spectrum disorders (ASD) is still one of today's challenges.The aim of the study:Review the research regarding the content of individual trace elements and toxic elements in the hair and in the serum of autistic children.Material and method:Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: autism, ASD, trace elements, toxic elements.Description: There are significant differences in the concentrations of essential trace elements and levels of toxic metals in hair and serum in children with autism spectrum disorders compared to healthy children. Many children with autism spectrum disorders suffer from a deficiency of essential trace elements (including Zn, Cu, Mn, Mo, J, Ni, Cr and others) and high toxic metal loads (Pb, Hg, Cd, Al.).Summary: The deficiency of essential trace elements and the presence of toxic heavy metals seem to play an important role in the pathogenesis and severity of autistic disorders.